Examining the relationship between countermovement and squat jump measures amongst elite development female football and rugby players - Collins, J.; Parker, J. K.; McKean, M.; Lovell, G. P.; Hogarth, L. (International Journal of Strength and Conditioning, 2023)
Purpose: In response to the need for a single low cost, relatively quick, minimally invasive test of strength, power, and velocity for elite development standard female football and rugby players requiring minimal staff expertise and sophisticated equipment, with benchmark standards, this study had two aims. Firstly, how countermovement jump (CMJ) and squat jump (SJ) tests associate with commonly used football and rugby strength and velocity tests. Secondly, to propose benchmark standards for elite development level female football and rugby players.